Polylactide single-polymer composites with a wide melt-processing window based on core-sheath PLA fibers. (5th February 2018) - Liu, Qingsheng; Zhao, Mingming; Zhou, Yuqi; Yang, Qibing; Shen, Ying; Gong, R. Hugh; Zhou, Fenglei; Li, Yuhao; Deng, Bingyao
Abstract: Polylactide (PLA) single polymer composites (SPCs) were prepared using PLA nonwovens made of core-sheath PLA fibers as raw materials by hot-pressing. The core and sheath materials were poly(l -lactide) (PLLA) and PLA withd -lactide of about 10 mol% (PLA90), respectively. The melt processing window of PLA SPCs reached more than 40 °C. The effects of hot-pressing temperature on the crystallinity, the size distribution of crystallites, the lamellar thickness and mechanical property of PLA SPCs were significant while those of hot-pressing pressure were small. The strong interfacial adhesion between matrix and reinforcement led to high mechanical properties of PLA SPCs. For pure PLA materials prepared at 180 °C, the tensile strength ( σb ), elongation at break ( εb ), the work of rupture ( W) and impact strength ( αcU ) were only 19 MPa, 1.8%, 0.15 J, and 2.8 kJ/m 2, respectively while those of the SPCs prepared at 130–160 °C were 47–65 MPa, 15–32%, 9–22 J, and 14.9–67.2 kJ/m 2, respectively. With the increase of hot-pressing temperature, the σb, W and αcU decreased. Graphical abstract: Highlights: PLA single polymer composites are prepared using PLA nonwovens made of core-sheath PLA fibers as raw materials. PLA single polymer composites can be prepared on industrial scale. The melt processing window of PLA single polymer composites is more than 40 °C. PLA single polymer composites have excellent mechanical properties.